Change Management and Sustainable Growth Rate: Evidence of the Banking Sector in Angola between 2013 and 2023 - Ken Kalala Ndalamba; Nelma Irene Cardoso Manuel (Public Governance, Administration and Finances Law Review, 2025)
Effective change management creates value for firms prepared to respond to market challenges robustly and forthrightly to gain competitive advantage. This study identifies the role of effective change management in promoting the capabilities of firms to remain sustainable and resilient amid economic crises. After engaging with the concept of crises and change management, this study analyses the banking sector in Angola with a particular focus on commercial banks. The financial statements of banks were scrutinised over the period between 2013 and 2023 with a view to determine the Sustainable Growth Rate (SGR), which is considered an indicator of sustainability and resilience. Only four banks managed to successfully navigate through the roller-coaster period of crisis with a positive SGR throughout the period of analysis. This case study attempts to bridge theories and praxis to inform both scholars and practitioners. The study concludes by identifying four important contributions and suggesting opportunities for further research and application.